CSR as a Social Activity and Islamic Performance Index on The Profit Growth of Islamic Bank in Supporting Economic - Annisya, Lusy; Oktaviana, Ulfi Kartika (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
Earnings growth is an indicator of company performance by using previous period earnings to calculate future earnings. Measures managerial efficiency in the economy of operating companies. There are several factors that can affect the profit growth of Islamic banks in general, including CSR as a corporate responsibility activity towards social and islamicity performance index. The purpose of this study is to determine whether the social activities of Islamic banks through CSR are able to influence the increase in profit or profit growth. The research method in this study is descriptive quantitative method. The population in this study is an Islamic bank in Indonesia. The sampling technique uses purposive sampling, namely Islamic banks registered with the Financial Services Authority and reporting annual financial reports from 2015 to 2022, so the sample in this study was 7 Islamic banks. The data used in this study are secondary data obtained from the financial statements of each bank sampled, CSR data obtained from the disclosure of CSR activities in the financial statements covering 8 dimensions of corporate social responsibility measurement GRI indicators, namely: Vision & Mission Statement, Board of Directors and Top Management, Products and Services, Zakat, Charity, and Benevolent Funds, Commitment to employees, Commitment to debtors, Commitment to customers, and Sharia Supervisory Board or DPS Sharia reported, and calculate the formula for each variable.Â Data analysis in this study used panel data regression, and the model chosen was the fixed effect model. The data analysis technique in this study is panel data analysis (chow test, hausman test, classical assumption test, f test, t test, and coefficient of determination).Â The results showed that partially CSR social activities affect the profit growth of Islamic commercial banks in Indonesia, namely by helping the community in financial management, education, economy, health, environment, and transparency, Islamic banks can build a good image in the eyes of the community and strengthen relationships with stakeholders, which can have a positive effect on the profitability of Islamic banks. Islamicity Performance Index has no effect on the profit growth of Islamic commercial banks in Indonesia. And in the simultaneous test CSR and Islamicity Performance Index simultaneously affect profit growth.Keywords: Profit Growth, CSR, Islamicity Performance Index.